Free-running 9.1-μm distributed-feedback quantum cascade laser linewidth measurement by heterodyning with a C18O2 laser - Weidmann, D.; Joly, L.; Parpillon, V.; Courtois, D.; Bonetti, Yargo; Aellen, Thierry; Beck, Mattias; Faist, Jérôme; Hofstetter, Daniel (My University, 2003)
We report spectral linewidth measurements of a 9.1-μm distributed-feedback quantum cascade laser (QCL). The free-running QCL beam was mixed with a waveguide isotopic C18O2 laser onto a high-speed HgCdTe photomixer, and beat notes were recorded from a radio-frequency spectral analyzer. Beating was performed at two operating conditions, first near the QCL laser threshold (beating with the C18O2R10 line) and then at a high injection current (beating with the C18O2R8 line). Overall, beat note widths of 1.3–6.5 MHz were observed, which proves that a free-running QCL can have a short-term spectral width near 1 MHz.